2018
DOI: 10.1016/j.ijcard.2018.05.131
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of atrial fibrillation in different socioeconomic regions of China and its association with stroke: Results from a national stroke screening survey

Abstract: The prevalence of AF has increased in recent years, and it was positively correlated with socioeconomic status, sex (women), location (rural areas), and stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 36 publications
2
49
0
Order By: Relevance
“…A previous study demonstrated that 1.13% of younger people (<50 years of age) have AF in China. 19 In the present study, most of the patients had a small LAD and were at higher risk for AF recurrence. 19 Electrical reconnection of one or more PV may also play an important role in the late recurrence of AF.…”
Section: Discussionmentioning
confidence: 49%
“…A previous study demonstrated that 1.13% of younger people (<50 years of age) have AF in China. 19 In the present study, most of the patients had a small LAD and were at higher risk for AF recurrence. 19 Electrical reconnection of one or more PV may also play an important role in the late recurrence of AF.…”
Section: Discussionmentioning
confidence: 49%
“…In the general Asian population, it ranges from 0.4% to 1.5%,4 a lower rate than the 1%–2% reported by the ESC 2010 21 22. However, it remains lower than the recently reported national level of 2.31% in people aged 40 years and above 11. AF prevalence remained unchanged compared with that of a previous study conducted in rural areas of northeast China in 20138 despite China experiencing rapid social and economic progress, populating ageing and lifestyle changes.…”
Section: Discussionmentioning
confidence: 67%
“…AF prevalence is higher in men than in women over all age groups in northeast China, consistent with a previous report. 23 This sex-related difference might be due to lifestyle changes and distribution of environmental risk factors over time between men and women 11. However, we did not find a significant difference between urban and rural areas; thus, the urban–rural convergence of AF prevalence is possibly due to rapid urbanisation of rural populations with consequent lifestyle changes.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…As was shown in a recent survey published in China at the national level, the standardized overall prevalence of atrial fibrillation (AF) among the Chinese adults aged ≥40 years was 2.31% (95% CI: 2.28-2.33%). Additionally, there was a higher probability that participants with AF would have a stroke than those without AF (9.48% vs 2.26%, P < 0.001) [1]. According to the GARFIELD-AF registry with 2-year follow-up, the percentage (95% CI) of all-cause mortality, stroke or systemic embolism, and major bleeding (first occurrences) was 3.84 (3.68; 4.02), 1.27 (1.18; 1.38), and 0.71 (0.64, 0.79) per 100 person-years [2].…”
Section: Introductionmentioning
confidence: 97%